When Do Research Consortia Work Well and Why? Evidence from Japanese Panel Data - Branstetter, Lee G; Sakakibara, Mariko (American Economic Review, 2002)
We examine the impact of a large number of Japanese government-sponsored research consortia on the research productivity of participating firms by measuring their patenting in the targeted technologies before, during, and after participation. Consistent with the predictions of the theoretical literature on research consortia, we find consortium outcomes are positively associated with the level of potential R&D spillovers within the consortium and (weakly) negatively associated with the degree of product market competition among consortium members. Furthermore, our evidence suggests that consortia are most effective when they focus on basic research.